Suggestopedia Meets Multisensory Learning: A Synergistic Approach to Boosting Children's Creative Thinking and Expressive Language - Sahlan (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
Students must think creatively and communicate well. Students who fail to share their thoughts and discoveries may lack confidence and perform poorly in social situations. This study analyses how multisensory suggestopedia boosts student creativity and expressive language. This quantitative experiment uses non-equivalent control groups and explanations. This study featured 30 control and 30 experimental students. A sample of grade 1 elementary school students was chosen for the study. This study included questionnaires and observation checklists. A 12-item children's creative thinking questionnaire and an 8-item expressive language instrument were used in this study. This study tested normalcy and homogeneity. Data was further analyzed using SPSS with an independent sample t-test. Multimodal suggestopedia learning increased students' language and creative thinking, according to one study. Creative thinking and expressive language scores were high in the experimental group: 32.8 > 17.5 and 25.55 > 14.5. Additionally, each variable has a significance value of 0.000 < 0.05. The optimistic suggestions in Suggestopedia facilitate multisensory learning by engaging students' senses. Students' ability to think creatively and articulate their ideas has grown. Future students may benefit from Suggestopedia and other multisensory learning tools.